2006
DOI: 10.1079/bjn20061849
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic and hypolipidaemic properties of ginger ( Zingiber officinale) in streptozotocin-induced diabetic rats

Abstract: In the present study, the hypoglycaemic potentials of ginger (Zingiber officinale) were studied in rats. An aqueous extract of raw ginger was administered daily (500 mg/kg, intraperitoneally) for a period of 7 weeks to streptozotocin (STZ)-induced diabetic rats. Fasting blood serum was analysed for blood glucose, cholesterol and triacylglycerol levels. The STZ-injected rats exhibited hyperglycaemia accompanied with weight loss, indicating their diabetic condition. At a dose of 500 mg/kg, raw ginger was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
225
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(247 citation statements)
references
References 36 publications
19
225
1
2
Order By: Relevance
“…This glycation lowering activity can be linked to the presence of various phenolic components in ginger rhizomes. The pungent fractions of ginger, namely gingerols, shogaols, paradols, and volatile constituents like sesquiterpenes and monoterpenes, are mainly attributed to the healthenhancing perspectives of ginger (Al-Amin et al, 2006;Ojewole, 2006;Islam, Choi, 2008;Butt, Sultan, 2011). The NEG inhibitory activity of ginger depends, at least in part, on its ability to trap reactive carbonyl intermediates in NEG/AGE formation, thereby inhibiting the chemical modification of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This glycation lowering activity can be linked to the presence of various phenolic components in ginger rhizomes. The pungent fractions of ginger, namely gingerols, shogaols, paradols, and volatile constituents like sesquiterpenes and monoterpenes, are mainly attributed to the healthenhancing perspectives of ginger (Al-Amin et al, 2006;Ojewole, 2006;Islam, Choi, 2008;Butt, Sultan, 2011). The NEG inhibitory activity of ginger depends, at least in part, on its ability to trap reactive carbonyl intermediates in NEG/AGE formation, thereby inhibiting the chemical modification of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have mentioned antidiabetic activity of Zingiber officinale (Grover et al, 2002;Akhani et al, 2005;Kelble, 2005;Al-Amin et al, 2006;Büyükbalci, Sedef, 2008;Islam, Choi, 2008;Abd-Elraheem et al, 2009;Saraswat et al, 2009;Ogbera et al, 2010;Saraswat et al, 2010;Madkor et al, 2011;Ramudu et al, 2011;Rani et al, 2011), no data is available on protein glycation and glucose absorption inhibitory potential of native Zingiber officinale rhizomes at national level. The present study was undertaken to investigate the antidiabetic effects of Zingiber officinale in terms of glucose diffusion and glycation inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Ginger contains several compounds and enzymes including gingerdiol, gingerol, gingerdione and shogaols (Rivlin, 2001;Zhao et al, 2011). These compounds have been reported to have antimicrobial, antioxidative and pharmacological effects (Al-Amin et al, 2006;Tapsell et al, 2006;Ali et al, 2008). Garlic is best known as a spice and herbal medicine for treatment and prevention of an array of diseases (Adibmoradi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cumin and ginger have many proven nutraceutical properties including stomachic, diuretic, carminative, emmanogogic, antispasmodic, antimicrobial and hypoglycaemic properties [26]. Al Amin et al [27] found that raw ginger possessed hypoglycaemic, hypocholesterolaemic and hypolipidaemic potential. Although the differences were not significant for the lipid profile and blood glucose levels, the present study supports this finding.…”
Section: Discussionmentioning
confidence: 99%